Strategic Integration of CSR and Human Resource Practices: Effects on Employee Empowerment and Social Identity in Higher Education - Alam, Mohammad Zulfeequar; Parween, Shaista; Abdullah, Shamsul Nahar; Silawi, Abdullah; Fatima, Zainab (Journal of Cultural Analysis and Social Change, 2025)
The significance of social identity in the workplace for affecting worker involvement and organizational results cannot be overstated. Nevertheless, there is a shortage of research that emphasizes the relationship between social identification in higher education institutions (HEI) and Corporate Social Responsibility (CSR). Knowing how these programs affect workers’ sense of belonging to their employer and coworkers becomes critical as HEI emphasizes CSR as a component of their organizational principles. With an emphasis on the function of CSR, this study investigates the patterns of social identity at work in the setting of HEI. The study used the SEM-PLS approach to collect information regarding 380 workers at a HEI through an online survey. Overall, the results support the hypothesis that HEI's CSR development programs have an impact on study-related attitudes by demonstrating a substantial correlation between CSR and career fulfillment, involvement at work, and organizational identity. Additionally, the study discovers that CSR programs improve psychological empowerment among employees and have a beneficial impact on their perceptions of supportiveness. The results reaffirm that HEIs must combine human resource and CSR initiatives and give CSR communication approaches particular consideration. These results highlight the need for HEI to design successful CSR programs that improve employees' general well-being as well as their perceptions of empowerment and career fulfillment. This study helps to mitigate the paucity of research on the effects of CSR on workers’ performance.